Evaluation of Teacher Professional Education Program (PPG) Teaching Graduates in Edge Area, Front Area, and Left Side Area of Indonesia (SM-3T) of Universitas Negeri Padang - Syaiful Haq; M Giatman; Azwar Inra (Postgraduate School, Universitas Negeri Padang, 2019)
The low percentage of 2017 PPT 3T SMT graduates (41.26%) in the National Examination and there are several study programs that did not pass (0%) causing this program to be evaluated. Based on the existing problems, this program must be comprehensively evaluated using the context, input, process & product (CIPP) model. In addition, capability evaluation is an absolute capability that must be possessed by humans in the era of industrial revolution 4.0. This evaluation study (